Financial technology and inclusion in ASEAN - FERNANDEZ, David (Institutional Knowledge at Singapore Management University, 2020)
Financial technology (FinTech) has the potential to be a positive, game-changing force for boosting financial inclusion in ASEAN, as mobile money and greater access to basic financial services have the capacity to improve the economic well-being of households. Indeed, technology has been shown to drive broader increases in economic growth, which itself interacts positively with financial inclusion. In a more direct way, new, specific fintech developments globally and in ASEAN itself can be beneficial for financial inclusion. In this paper, we look at financial inclusion and technology, and how cooperative efforts between ASEAN policymakers, the private sector, and their broader communities can promote financial stability and inclusive growth through the deployment of fintech applications supported by cloud-computing, big data analytics, the Internet-of-Things (IoT), Artificial Intelligence (AI), blockchain technologies and cryptocurrencies.